Mass spectrometry of protein interactions (Wiley-Interscience, 2007)
Mass spectrometry (MS) is playing an increasingly important role in the study of protein interactions. Mass Spectrometry of Protein Interactionspresents timely and definitive discussions of the diverse range of approaches for studying protein interactions by mass spectrometry with an extensive set of references to the primary literature. Each chapter is written by authors or teams of authors who are international authorities in their fields